1998
DOI: 10.1007/bfb0053984
|View full text |Cite
|
Sign up to set email alerts
|

Predicting application run times using historical information

Abstract: The Soudan 2 detector is used to search for evidence of nucleon decay. Particular emphasis is put on searches for modes with multiple-charged particles in the final st ate, and for modes suggested by super-symmetric theories.Mode

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(113 citation statements)
references
References 8 publications
0
110
0
3
Order By: Relevance
“…Workload traces have revealed that users tend to frequently resubmit similar or even identical jobs [9,10], a phenomenon that automated runtime predictors have leveraged in the past [11,22]. A symbiotic scheduler may utilize these same techniques to identify applications and associated resource bottlenecks.…”
Section: Identifying Symbiosismentioning
confidence: 99%
“…Workload traces have revealed that users tend to frequently resubmit similar or even identical jobs [9,10], a phenomenon that automated runtime predictors have leveraged in the past [11,22]. A symbiotic scheduler may utilize these same techniques to identify applications and associated resource bottlenecks.…”
Section: Identifying Symbiosismentioning
confidence: 99%
“…In the works by Smith et al [9] [10], runtime predictions are derived using similar runs in the history, and these estimates are further used to simulate the scheduling algorithms like FCFS, LWF (Least Work First) and Backfilling [11] to obtain the queue wait times predictions. Another work by Li et al [12] tries to improve the runtime prediction and simulate the batch system for the Maui scheduler [4].…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, their efforts use runtime estimates for the prediction of queue wait times. The runtime estimates reported in these efforts [9] [10] have high prediction errors from 33% to 74% in many cases, and hence using these estimates to predict queue wait times will lead to large errors in wait time predictions.…”
Section: Related Workmentioning
confidence: 99%
“…Since demand and supply of Grid services fluctuates in the course of time, information about current and future resource utilization and prices are often not known a-priori to the participants. In this case consumer and provider agents try to maximize their utilities by generating bids based on their valuations and historic experiences [6]. This results in strategic behavior on provider and consumer side.…”
Section: Automated Resource Allocationmentioning
confidence: 99%